Profit taxation, R&D spending, and innovation - Andreas Lichter; Max Löffler; Ingo Eduard Isphording; Thu-Van Nguyen; Felix Poege; Sebastian Siegloch (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
We study how profit taxation affects plants' R&D spending and innovation activities. Relying on geocoded survey panel data which approximately covers the universe of R&D-active plants in Germany, we exploit around 7,300 changes in the municipal business tax rate over the period 1987-2013 for identification. Applying event study models, we find a negative and statistically significant effect of an increase in profit taxation on plants' R&D spending with an implied long-run elasticity of 􀀀1.25. Reductions in R&D are particularly strong among more credit-constrained plants. In contrast, homogeneity of effects across the plant size distribution questions policy makers common practice to link targeted R&D tax incentives to plant size. We further find lagged negative effects on the (citation-weighted) number of filed patents.
Keywords: H25; H32; O31; O32; 330; corporate taxation; firms; R&D; innovation; patents